Voluntarism Rationality in Norway: The Relevance of Ferie for Alle - Asyraf, Muhammad Affan (Department of Anthropology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The article examines a voluntary phenomenon that exists in “Ferie for Alle”. The name refers to a voluntary-based program organized by the Norwegian Red Cross, a prominent NGO in Norway. The program is oriented in ensuring free holiday experiences for children and families who are deemed unfortunate. Interestingly such a regard is attached due to their inability to afford vacation trips during holiday time. This article aims to address why such phenomenon of Ferie for Alle able to emerges in Norwegian society and attracts people to volunteer to it. This paper uses an ethnographic approach. In specific, it utilizes qualitative method such as semi-structured in-depth interview for the data collection process, and narratives analysis for data analysis process. Through the result, this paper argues that the existence of voluntarism in Ferie for Alle is instigated by volunteers’ reasoning towards prominent social aspects, that is: (1) growing up experiences in Norwegian society, (2) interpretation of Norwegian culture (3) understanding of a certain Norwegian welfare provision discourse. Moreover, actualization of volunteering further gave an idea of how Norwegian welfare system is supposed to be conducted. As reflected by the Ferie for Alle volunteers, such meaning helps them navigate activism in addressing transnational political issues happening in Norway.